Hypo-glycaemia and Associated Factors among Type 1 Diabetes Mellitus Patients Attending the Outpatient Clinics of Debre-tabor Compressive and Specialized Hospital, South Gondar Zone, North West Ethiopia: A Cross-sectional Study - Yalgaw Zimamu, Libsuye; Mekete Adal, Gashaw; Mehiret Wubet, Gashaw; Alemnew, Dessie (Journal of Community Medicine and Health Solutions, 2024)
Introduction: Hypoglycemia affects patient safety and glycemic control during insulin treatment of both type 1 (T1DM) and type 2 diabetes mellitus (T2DM). It is still a major clinical problem in the treatment of type 1 diabetes that impairs metabolic control. This study aimed to assess hypoglycemia and associated factors among type 1 diabetes mellitus patients attending the outpatient clinics of Debra–Tabor Comprehensive and Specialized Hospital, in 2021. Method: institutional-based cross-sectional study design was conducted among 204 selected type I DM, from June 1/2021 to August 30/2021. The study participants were selected by systematic sampling method from monthly follow-up lists and lists of registration. Data were cleaned and entered into Epi Data and then exported into SPSS version 20 for analysis. Data were presented with texts, graphs, diagrams, and tables but an analytic form of findings will be presented by text form of the odds ratio. Bivariable and multivariable binary logistic regression models were fitted to identify factors associated with hypoglycemia p – value < 0.05 was considered statistically significant and reported as a 95% confidence interval (CI). Results: A total of 204 participants participated with a response rate of 100% and prevalence of self-reported hypoglycemia was 88.7% (95%, CI: 83.8-92.6) and the prevalence of hypoglycemia was significantly associated with occupation [AOR: 4.01 (95% CI:1.86-9.35)], higher educational status [AOR: 2.13 (95% CI:1.92-13.15)], diabetic duration < 1 [AOR: 3.80 (95% CI:1.32-9.28)], poor knowledge [AOR: 4.91 (95% CI:1.09-11.06)] and favorable attitude [AOR: 5.86(1.10-6.07)]. The current study revealed that the knowledge, attitude, and practice of respondents were 81.9% (95%, CI, 76-86.8), 73% (95% CI, 66.7-78.9), and 91.2% (95% CI, 86.8-94.6) respectively Conclusion and recommendation: Hypoglycemia was highly prevalent among diabetic patients treated at Debra-Tabor Comprehensive and Specialized Referral Hospital. To reduce the higher prevalence of hypoglycemia the health professionals working in the hospital had better provide appropriate patient advice about, BGL monitoring, medication adherence, self-injection as well as oral hypoglycemic agent administrations.